A Critical Analysis of The Existence of Da’if Hadith (Weak Hadith) in Ṣaḥiḥ al-Bukhari - Habiburrahman Rizapoor; Mohammad Anwar Zafari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aims to find out whether all the hadiths narrated in Ṣaḥiḥ al-Bukhari are valid and correct or there are also ḍa’if and weak hadiths. In this article, the researcher has used the descriptive and content analysis method by referring to scientific articles, books of principles of hadith. Hadith annotation books and other books in which the subject has been discussed. In this article, the writer discusses the views and arguments of the scholars who claim that there are consensuses that the book of Ṣaḥiḥ al-Bukhari is the most correct book after the Qur’an and there is no ḍa’if hadith in it. Similarly, the writer discusses the views of the scholars who argue that all the hadiths of Ṣaḥiḥ al-Bukhari are not authentic and there are hadiths in Ṣaḥiḥ al-Bukhari which are not authentic and are ḍa’if. By considering the arguments of both sides, the writer concludes that Ṣaḥiḥ al-Bukhari is the most correct book after the Holy Qur’an, nevertheless, this does not mean that there are no ḍa’if hadiths in Ṣaḥiḥ al-Bukhari and there are many hadiths that are called ḍa’if by the scholars of hadith. Also, the existence of ḍa’if hadiths in the book of Ṣaḥiḥ al-Bukhari does not decrease the scientific ranking and status and level of acceptance of the book and prophetic hadith among the ummah and scholars of Hadith